Study and analysis of single notched rectangular dielectric resonator antenna for cognitive radio applications - Nagendram, S; T P Madhav, B; Sony, K; Janaki, P; Lakshmi Prasanna, P; Swetha, S; Venkateswara Rao, M; ., . (International Journal of Engineering and Technology, 2017)
Â In this article a single notched ultra-wideband antenna which is integrated with dielectric ring resonator is proposed for cognitive radio applications. The proposed antenna consists of elliptical base and a split ring resonator on either side of the feedline for bandwidth enhancement. The rectangular dielectric resonator which is proposed is a rectangular dielectric resonator which give good isolation between the two ports. The proposed antenna has single rejection at 5.7GHz-8.4GHz at ultrawideband region. The proposed antenna has a peak gain of 6dB and average gain of 3. 1dB.Commercially equipped tool ANSYS EM 17 is used to characterise the proposed antenna. The proposed antenna provides good isolation between the two antenna ports confirming efficient integration. The antenna is best suitable for candidate of radar applications, medical imaging and cognitive radio systems.